The metagenomic and whole-genome metagenomic detection of multidrug-resistant bacteria from subclinical mastitis-affected cow’s milk in India - Manimaran, Ayyasamy; Desingu, Perumal Arumugam; Kumaresan, Arumugam; Singh, Poonam; Subramanya, Komala; Dodamani, Pramod; Dineshbhai, Parmar Ankitkumar (Frontiers in Cellular and Infection Microbiology, 2025)
Multidrug-resistant (MDR) bacteria in farm animal products threaten human health by causing zoonotic infections. The complete genome sequences of MDR bacteria from subclinical mastitis-affected cow’s milk have not yet been comprehensively documented in India. In this study, using a bacterial metagenomic sequencing approach, we detected the nearly complete genome sequences of Pseudomonas veronii and Staphylococcus xylosus from subclinical mastitis-affected cow’s milk. Furthermore, we sequenced the nearly complete genome sequences of Escherichia coli, Klebsiella pneumoniae, Staphylococcus hominis, and S. xylosus from subclinical mastitis-affected cow’s milk using a whole-genome metagenomic sequencing method. Our analysis subsequently revealed that the complete genome sequences of the identified bacteria contained MDR genes and genes for multiple virulence factors. These MDR bacteria may pose a public health risk through exposure to milkers, milk handlers, and farm workers or through the handling and consumption of unpasteurized milk.